An Intelligent Active Force Control Algorithm to Control an Upper Extremity Exoskeleton for Motor Recovery - Wan Hasbullah, Mohd Isa; Zahari, Taha; Ismail, Mohd Khairuddin; Anwar, P. P. A. Majeed; Khairul Fikri, Muhammad; Ali, Mohammed A. H.; Jamaluddin, Mahmud; Zulkifli, Mohamed (IOP Publishing, 2016)
This paper presents the modelling and control of a two degree of freedom upper extremity exoskeleton by means of an intelligent active force control (AFC) mechanism. The Newton-Euler formulation was used in deriving the dynamic modelling of both the anthropometry based human upper extremity as well as the exoskeleton that consists of the upper arm and the forearm. A proportional-derivative (PD) architecture is employed in this study to investigate its efficacy performing joint-space control objectives. An intelligent AFC algorithm is also incorporated into the PD to investigate the effectiveness of this hybrid system in compensating disturbances. The Mamdani Fuzzy based rule is employed to approximate the estimated inertial properties of the system to ensure the AFC loop responds efficiently. It is found that the IAFC-PD performed well against the disturbances introduced into the system as compared to the conventional PD control architecture in performing the desired trajectory tracking.